Human Papillomavirus Vaccine Effectiveness Against Incident Genital Warts Among Female Health-Plan Enrollees, United States. Issue 2 (21st June 2017) - Hariri, Susan; Schuler, Megan S; Naleway, Allison L; Daley, Matthew F; Weinmann, Sheila; Crane, Bradley; Newcomer, Sophia R; Tolsma, Dennis; Markowitz, Lauri E
Abstract: We examined the effectiveness of human papillomavirus vaccination by dose number and spacing against incident genital warts in a cohort of 64, 517 female health-plan enrollees in the United States during 2006–2012. Eligible recipients were classified into groups by regimen: 0, 1, 2 (<6 months apart), 2 (≥6 months apart), or 3 doses. They were followed until a genital wart diagnosis, loss to follow-up, or the end of study. Propensity score weights were used to balance baseline differences across groups. To account for latent genital warts before vaccination, we applied 6- and 12-month buffer periods from last and first vaccine dose, respectively. Incidence rates and hazard ratios were calculated using Poisson regression and Cox models. The propensity score–weighted incidence rate per 100, 000 person-years was 762 among unvaccinated participants. Using 6- and 12-month buffer periods, respectively, incidence rates were 641 and 257 for 1 dose, 760 and 577 for the 2-dose (<6-month interval) regimen, 313 and 194 for the 2-dose (≥6-month interval) regimen, and 199 and 162 among 3-dose vaccinees; vaccine effectiveness was 68% and 76% for the 2-dose (≥6-month interval) regimen and 77% and 80% in 3-dose vaccinees compared with unvaccinated participants. Vaccine effectiveness was not significant among vaccinees receiving 1-dose and 2-dose (<6-month interval) regimens compared with unvaccinated participants. Our findings contribute to a better understanding of the real-world effectiveness of HPV vaccination.